A multiplex single nucleotide polymorphism genotyping method using ligase‐based mismatch discrimination and CE‐SSCP. Issue 8 (3rd March 2014) - Choi, Woong; Shin, Gi Won; Hwang, Hee Sung; Pack, Seung Pil; Jung, Gyu Yong; Jung, Gyoo Yeol
<x xml:space="preserve">Abstract</x> Accuracy, simplicity, and cost‐effectiveness are the most important criteria for a genotyping method for SNPs compatible with clinical use. One method developed for SNP genotyping, ligase‐based discrimination, is considered the simplest for clinical diagnosis. However, multiplex assays using this method are limited by the detection method. Although CE has been introduced as an alternative to error prone microarray‐based detection, the design process and multiplex assay procedure are complicated because of the DNA size‐dependent separation principle. In this study, we developed a simple and accurate multiplex genotyping method using reaction condition‐optimized ligation and high‐resolution CE‐based SSCP. With this high‐resolution CE‐SSCP system, we are able to use similar‐sized probes, thereby eliminating the complex probe design step and simplifying the optimization process. We found that this method could accurately discriminate single‐base mismatches in SNPs of the tp53 gene, used as targets for multiplex detection.